Implementation of Youth Policy in the Context of Digitalization of the Union State of Russia and Belarus - A. I. Velichko (Евразийская интеграция: экономика, право, политика, 2025)
Aim and tasks. The purpose of this study is to assess the current state and prospects for the implementation of youth policy in the Union State of Russia and Belarus in the context of accelerated digitalization. The analysis focuses on the legal, institutional, technological, and socio-political aspects of youth engagement. Special attention is paid to the impact of digital transformation on the participation, education and employment opportunities of young citizens. Methods. The methodological basis of the research is based on comparative political analysis, generalization of statistical data and structural analysis of regulations and national strategies. Results. The results of the study indicate that both States have a comprehensive regulatory framework and a strong political commitment to youth development. However, the integration of digital tools into youth policy remains fragmented due to regional infrastructural differences, insufficient harmonization of digital governance mechanisms, and the lack of a single supranational coordination platform. The results of the study show that the further development of youth policy requires systematic efforts to improve digital literacy and cyber resilience, create an integrated digital environment for joint youth initiatives, and implement real-time monitoring and data management. Conclusions. The author concludes that it is necessary to bring together the regulatory framework, cross-sectoral cooperation and strategic investments in digital infrastructure in order to transform youth policy into a driving force for integration and innovation throughout the Union State. The research can be continued by studying comparative models of supranational youth governance and conducting an interdisciplinary assessment of the socio-political impact of digitalization on youth identity and civic participation.